Sexual politics and resistance to law reform: a critique of the South African Law Commission report on women and sexual offences in South Africa - Hall, Colleen Helen (Institute of Criminology, 2021)
In 1985 the South African Law Commission published a Report entitled Women and Sexual Offences in South Africa. 1 The Report is the result of almost 3 years' research initiated at the request of the Minister of Justice in 1982. During the period 1979-1981 public attention in South Africa was drawn dramatically to the crime of rape. Media reports focused on the high incidence and brutality of the crime and contributed towards a heightened sense of public anxiety and outrage. Slabbert has argued convincingly that during this period the South African public experienced a “moral panic” regarding rape. Public concern extended to concern for the fate of rape victims and their treatment by the criminal justice agencies. This concern was voiced in Parliament. Questions were put to the Minister regarding the procedures involved in the laying of a rape charge and the medico-forensic aspects of the crime. As a result the Minister requested the South African Law Commission to investigate these matters. The resultant Report was published in April 1985.